Averting institutional disasters? Drawing lessons from China to inform the Cypriot response to the COVID‐19 pandemic. (12th September 2020) - Petridou, Evangelia; Zahariadis, Nikolaos; Ceccoli, Stephen
Abstract: Using 't Hart's (2014) typology of crises, we explore the Republic of Cyprus's initial response to the COVID‐19 crisis and contend Cypriot leaders indirectly drew lessons from the Chinese experience to prevent a situational crisis from metastasizing into a much broader institutional crisis. The lessons Cyprus drew from China to secure this outcome reinforced the critical nature of transparency and timeliness in sharing epidemiological information, swift intervention efforts to minimize virus transmission, and privileging expert involvement in shaping the response plan. We conclude with implications for public leadership and lesson‐drawing under crisis.